The Use Of Commercial Oxygen Probes During The Production Of High Titania Slags - J. M. A. Geldenhuis (The Southern African Institute of Mining and Metallurgy, 1999)
This work is concerned with studying possible reactions in the ilmenite furnace which may control the product quality of both slag and metal. Two different approaches were followed: comparing actual furnace slag compositions with the calculated equilibrium values and using commercial oxygen probes to measure the effective partial oxygen pressure in the slag and metal. It appears from a comparison of actual furnace slag compositions (in terms of the distribution coefficient of vanadium) with equilibrium values, that the TiO1.5-TiO2reaction may fix the effective partial oxygen pressure for the vanadium reaction. This possibility was tested using commercial oxygen probes (traditionally applied during steelmaking) to measure the effective oxygen partial pressure of both the slag and liquid iron in Iscor?s 3MVA pilot plant ilmenite furnace. From these measurements, it appears that commercial oxygen probes containing zirconia solid electrolytes can be used to measure the effective oxygen potential of both the slag and liquid iron. This oxygen activity correlates well with the FeO content of the slag. The results, furthermore, clearly illustrate that equilibrium conditions are not attained in the ilmenite furnace during the production of high titania slags, since the effective oxygen potential of slag and metal differ substantially.